IMPLEMENTASI NILAI-NILAI PENDIDIKAN ISLAM DALAM AKTIVITAS REMAJA MASJID IMAM RIJALI IAIN AMBON - Sadila Salma Walalayo (IAIN Ambon, 2021)
Abstract: The result of this study that the from of the Rijali IAIN Ambon Imam mosque youth programs that contains, the value of Islamic education is . 1). Preaching or preachers programs, Islamic studies programs, Community comford programs, Cooperative programns and government programs. This programs was formed by means of deliberations between the chairman of the Takmir mosque, the youth of the mosque, and other members. 2). Activities that contain the value of Islamic education including for women there are certain assignments including: a). cleaning the veil, b). reviewing women’s jurisprudence studies, c). training young preachers training, d). lecturing training, e). tahlil training, f). yasinan, g). cult before zhuhur prayer as well as Islamic studies, and big day celebrations Islamic. The implementation of Islamic values contained in the activities of the youth of the Imam Rijali IAIN Ambon mosque itself includes character formation, monotheism, worship n the morals. Islamic values are implemented through the program activities that exist in the youth mosque the Imam of the Ambon. Including the student component itself which was fully supported by the head of the mosque’s takmir Rijali IAIN Ambon. Keywords: Implementation of Islamic values, Adolescent mosque. Abstrak: Hasil penelitian ini bahwa bentuk program Remaja Masjid Imam Rijali IAIN Ambon adalah, 1). Program dakwah atau mubaligh, Program kajian keIslaman, Program kenyamanan umat, Program koperasi dan Program keputrian. Program-program ini dibentuk dengan cara bermusyawarah antara ketua takmir masjid, ketua remaja masjid dan para anggota lainnya. 2). Aktivitas yang mengandung nilai pendidikan Islam diantaranya untuk para akhwat ada tugas-tugas tertentu antara lain: a).Pembersihan mukena-mukena,b).Kajian - kajian fiqih wanita, c). Pelatihan-pelatihan mubaligh-mubaligh muda, d). Pelatihan ceramah, e). Pelatihan tahlil, f). Yasinan, g). Kultum sebelum shalat zhuhur serta kajian-kajian keIslaman, dan perayaan hari-hari besar Islam. Implementasi nilai-nilai Islam yang terdapat dalam aktivitas remaja masjid sendiri yaitu meliputi pembentukan karakter, ketauhidan, ibadah serta akhlak. Nilai-nilai Islam itu di terapkan melalui aktivitas program yang ada di Remaja Masjid Imam Rijali IAIN Ambon tersebut. Dengan adanya implementasi nilai-nilai Islam ini sangat mempengaruhi bagi remaja masjid termasuk didalamnya komponen mahasiswa itu sendiri yang sepenuhnya mendapat dukungan ketua takmir masjid. Kata kunci: Aktivitas Remaja Masjid, Nilai-Nilai Pendidikan Islam